2019
DOI: 10.3390/w11010143
|View full text |Cite
|
Sign up to set email alerts
|

Time-Averaged Turbulent Velocity Flow Field through the Various Bridge Contractions during Large Flooding

Abstract: Extreme rainfall events, larger than 500-year floods, have produced a large number of flooding events in the land and also close to the shore, and have resulted in massive destruction of hydraulic infrastructures because of scour. In light of climate change, this trend is likely to continue in the future and thus, resilience, security and sustainability of hydraulic infrastructures has become an interesting topic for hydraulic engineering stakeholders. In this study, a physical model experiment with a geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…These differences have a direct impact on the scour depth and its temporal evolution and showed that accumulation with larger equivalent roughness height would generate deeper scour. A recent study [31] analyzed the flow dynamic of bridges in pressure-flow conditions, but this study focused on the combined impact of pressure flow and abutment scour, which presents important differences compared to pier scour.…”
Section: Introductionmentioning
confidence: 99%
“…These differences have a direct impact on the scour depth and its temporal evolution and showed that accumulation with larger equivalent roughness height would generate deeper scour. A recent study [31] analyzed the flow dynamic of bridges in pressure-flow conditions, but this study focused on the combined impact of pressure flow and abutment scour, which presents important differences compared to pier scour.…”
Section: Introductionmentioning
confidence: 99%
“…The approach section of the pier model was 15.0 m long followed by a working mobile bed section with a length of 3.0 m in which the pier model was placed. The length of the approach section was decided based on the findings from other researches [25][26][27][28][29] to ensure a fully developed approach turbulent flow and turbulent boundary layer at the bridge pier. After the working mobile bed section, additional 3 m long sediment trap section downstream of the pier model was placed.…”
Section: Methodsmentioning
confidence: 99%
“…The simultaneous influence of such processes as the unsustainable movement of water medium and river structures; the existence of significant areas with turns; re-formation of watercourse and floodplain shape in the process of deformation leads to the development of general and local washouts in the area of influence of bridge crossings. In order to study the devastating effects of natural floods as consequences of climate change, paper [2] represents laboratory research into a physical model -the area of river flow with a bridge crossing. Based on the conducted studies, it was concluded on the significant influence of a bridge crossing due to blocking the floodplain flow, corresponding re-formation and an increase in velocities, increased intensity of sediment transfer in the watercourse, at the same time, deformation processes on floodplains were not considered.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…In the expanded form equation 1and (2) are written down as follows: 2 3 3 1 3 2 3 1 2 3 2 3 1 3 2 3 3 3 1 2 3 1 ,…”
Section: The Aim and Objectives Of The Studymentioning
confidence: 99%
See 1 more Smart Citation